Risk factors for failure of the 36 mm metal-on-metal Pinnacle total hip replacement system: a retrospective single-centre cohort study - Matharu, G; Nandra, R; Berryman, F; Judge, A; Pynsent, P; Dunlop, D (British Editorial Society of Bone and Joint Surgery, 2017)
Aims: To determine 10-year failure rates following 36mm metal-on-metal (MoM) Pinnacle total hip replacement (THR), and identify predictors of failure. Methods: We retrospectively assessed a single-centre cohort of 569 primary 36mm MoM Pinnacle THRs (all Corail stems) followed up since 2012 according to MHRA recommendations. Allcause failure rates (all-cause revision, and non-revised cross-sectional imaging failures) were calculated, with predictors for failure identified using multivariable Cox regression. Results: Failure occurred in 97 hips (17.0%). The 10-year cumulative failure rate was 27.1% (95% CI=21.6%-33.7%). Primary implantation from 2006 onwards (Hazard Ratio (HR)=4.30; CI=1.82-10.1; p=0.001) and bilateral MoM hip arthroplasty (HR=1.59; CI=1.03-2.46; p=0.037) predicted failure. The effect of implantation year on failure varied over time. From 4-years onwards following surgery, hips implanted since 2006 had significantly higher failure rates (8-years=28.3%; CI=23.1%-34.5%) compared to hips implanted before 2006 (8- years=6.3%; CI=2.4%-15.8%) (HR=15.2; CI=2.11-110.4; p=0.007). Conclusion: We observed that 36mm MoM Pinnacle THRs have an unacceptably high 10-year failure rate, especially if implanted from 2006 onwards or in bilateral MoM patients. Our findings regarding implantation year and failure support recent concerns about the device manufacturing process. We recommend all patients undergoing implantation since 2006 and those with bilateral MoM hips undergo regular investigation, regardless of symptoms.